The results of intraoperative diluted hydrogen peroxide in empyema surgery - Aydin, Siyami; Cakmak, Muharrem (Bayrakol Medical Publisher, 2025)
Aim: Empyema is a dense, sticky inflammation of the pleural cavity. Many treatment approaches have been reported so far. A 3% hydrogen peroxide solution administered orally does not cause serious toxicity. We aim to share the effects of intraoperative intrapleural diluted 3% hydrogen peroxide on the surgical outcomes of patients who underwent decortication. Materials and Methods: Of patients who underwent decortication due to empyema, those with or without intraoperative, intrapleural administration of diluted 3% H2O2 were randomly selected and divided into two groups. A total of 36 patient cases were analyzed. Results: In terms of duration, the results of Group 1 were more significant compared to Group 2. Regarding postoperative drainage catheter removal, the results for Group 1 were more significant than Group 2. In terms of the mean hospital stay, the results of Group 1 were statistically more significant compared to Group 2 (p<0.05). Discussion: In patients with empyema with pleural thickening and loculations, the use of intraoperative intrapleural diluted 3% hydrogen peroxide shortens the mean operation time, time to removal of the drainage catheter, and hospital stay. It also has a positive effect on the recovery period.
Keywords: decortication; empyema; hydrogen peroxide; thoracotomy